(untitled) (Observatorio Económico, 2014)
The economic and social success of most modern economies rests mainly on innovation and the generation of new ideas. It is not surprising, then, that higher education, and university education in particular, plays a predominant role in a country’s development. Unfortunately, organizing a high-quality higher education system is far from similar to building a highway or a new subway line. Therefore, transferring the organizational foundations of private business activity to the university sector does not ensure quality education or relevant research. Continue reading...